The effects of procedural justice and distributive justice criteria on secondary school teachers' fairness appraisal - Pingul, Ferdinand S. (Animo Repository, 2008)
This study investigates the effects of procedural justice and distributive justice criteria on fairness appraisal. Two hundred thirty nine high school teachers from Bulacan, Cavite, and Pasig City participated. They rated the fairness of two justice scenarios, one organizational and one educational, each containing a procedural justice criterion (voice) and a distributive justice criterion (equity). Analyses of variance were performed. The results showed that process and distribution interact differently in the two scenarios- distributive justice affects fairness appraisal in the organization scenario while procedural justice affects fairness appraisal in the education scenario. These results indicate that as receivers of justice decisions, the participants are influenced by outcomes in appraising the fairness of a situation while as makers of decisions, they are influenced by processes.